MENGKAJI PERBANDINGAN POLA PERILAKU KONSUMEN DI PASAR MODERN (RETAIL) DAN DI PASAR TRADISIONAL - Purwanti, Nur Indah; Khoerunnisa, Resi; Prasetyanto, Ana Eka; Annisa, Fina Rizki (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The purposes of this study were to explain the behavior patterns of consumers in traditional and modern markets. The sampling criteria were: women, minimum age 17 years, and had shopped at the Surabaya traditional market or modern market. The result show that factors influence consumer to purchase in the traditional market were low price and strategic location andÂ in the modern market were comfortable, good layoutÂ and discounted price. The factors that affect consumers reluctant to shop in the traditional market were uncomfortable, unguaranty quality product, bad infrastructure and in the modern market were high price and no bargaining price.Â Keywords: modern market, traditional market, consumer behavior